Histoenzymic localization in the adenohypophyseal cells of pars distalis adenohypophysis of buffalo - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2014)
Different histoenzymic techniques were applied on the cryostat sections of the hypophysis cerebri of 12 apparently healthy animals of either sex. Demonstration of alkaline phosphatase, acid phosphatase, non-specific esterase and alpha-glycerophosphate dehydrogenases were studied. The intensities of most of these enzymes varied considenbly throughout the cytoplasm of almost all cells of buffalo pars distalis. The alkaline phosphatase activity was limited to blood vascular walls in the young calves. A weak to moderate reaction of acid phosphatase was localized in m.Jority of cells. The non specific esterase activity was weak to strong throughout the cytoplasm of almost all the cells of pars distalis and the reaction for alpha-glycerophosphate dehydrogenase was weak in young calves, strong in adults and cells surrounding the colloid mass had stronger reaction on luminal side in pregnant animals.